SYMPLECTIC REACTION IN OLIVINE AND THE CONTROLS OF INTERGROWTH SPACING IN SYMPLECTITES - Ashworth J.R.; Chambers A.D. (My University, 2000)
Symplectite growth is analysed in terms of non-equilibrium thermodynamics and maximum rate of energy dissipation. For a given reaction, the spacing λ of lamellae or rods is predicted to be proportional to the cube root of Lδ/v, where v is reaction rate and L is the Onsager diffusion coefficient of a reference element in the reaction front of width δ. The result is comparable with, but not identical to, metallurgical theory for discontinuous precipitation in alloys. It is reasoned that concentration-gradient constraints place a lower limit on λ, which depends on grain-boundary energy γ. An upper limit γ ~ 0·3 J/m2 is thus estimated using literature data from experimental oxidation of olivine. Combined with new observations on exsolution symplectites in olivine from the Lilloise intrusion, Greenland, this suggests that the exsolution reaction took place above 800°C. Using previous modelling of a corona with a symplectic layer, γ ~ 1 J/m2 is estimated for hornblende–spinel symplectite. The energy driving diffusion plus grain-boundary production in the reaction front was a small proportion of the overall affinity of the corona reaction. The theory explains symplectite growth over a wide range of igneous and metamorphic temperatures and timescales.